HAVE as a relation between individuals and properties - Bassaganyas Bars, T (Linguistic Society of America, 2018)
This paper argues that the role of HAVE-predicates is to introduce relations into the discourse, one of whose arguments is the individual denoted by the sentence subject. This is the only token-level argument in the relation: the other is modeled as a nominalized property (Chierchia, 1984; Chierchia and Turner, 1988). A number of peculiarities of HAVE are argued to follow from this account, including its connection with existential predicates (McNally, 1992, 2009).